Aryl borane as a catalyst for dehydrative amide synthesis - Gavit, Amit Vinayak; Talekar, Sanjana S.; Mane, Manoj V.; Sawant, Dinesh Nanaji (Journal of Organic Chemistry, 2025)
Tris(pentafluorophenyl)borane B(C6F5)(3)H2O is reported as a catalyst for dehydrative amidation of carboxylic acids and amines. This protocol is applicable across a wide range of >35 substrates, including aromatic and aliphatic amines and acids, resulting in amides in <= 92% yields. The scalability of the reaction up to 10 mmol, along with the synthesis of drugs such as ibuprofen amide, moclobemide, and phenacetin, demonstrates the industrial potential of our protocol.

Diboron reagents in modern reduction chemistry: a versatile tool for reduction of various functional groups - Gavit, Amit Vinayak; Darandale, Nutan Rajendra; Surange, Sarthak Baburao; Sawant, Dinesh Nanaji (Advanced Synthesis & Catalysis, 2025)
Reduction of various organic functionality including aldehyde, ketone, nitro, imine, and alkyne has gained noteworthy attention due to its vast application of products in organic transformation reactions. To attempt hydrogenation several approaches have been reported by using molecular hydrogen as a reducing source. Besides, this diboron (tetrahydroxy diboron, bispinacolato diboron, neoglycolato diboron) has shown a promising and alternative approach for the reduction of the reducible functional group without using any molecular hydrogen. The ligand-free reduction approach of commercially available diboron reduces the organic compound by using water or organic solvent and metal salt making it an attractive protocol in the recent era of reduction as well as hydrogenation. Herein, we provide an extensive and collective overview of the diboron-mediated reduction approach of various organic compounds.
Keywords: diboron; H2; H2O/MeOH; Metal; reduction